2012
DOI: 10.1007/s12253-012-9500-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression of GLUT1 and GLUT3 Glucose Transporters in Endometrial and Breast Cancers

Abstract: Cancer cells have accelerated metabolism and high glucose requirements. The up-regulation of specific glucose transporters may represent a key mechanism by which malignant cells may achieve increased glucose uptake to support the high rate of glycolysis. In present study we analyzed the mRNA and protein expression of GLUT1 and GLUT3 glucose transporters by quantitative real-time polymerase chain reaction (Q-PCR) and Western blotting technique in 76 cases of endometrial carcinoma and 70 cases of breast carcinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
141
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(153 citation statements)
references
References 22 publications
6
141
1
Order By: Relevance
“…Under physiological conditions, Glut3 is expressed predominantly in the brain tissue (2). The abnormal overexpression of Glut3 has been detected in numerous types of cancer, including breast, oral, lung, colon and bladder cancer, however, the underlying mechanism remains unclear (3)(4)(5)21). Given that mTORC1 signaling is also frequently activated in cancer, one hypothesis is that hyperactivated mTORC1 signaling may be responsible for the elevated Glut3 in these types of cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under physiological conditions, Glut3 is expressed predominantly in the brain tissue (2). The abnormal overexpression of Glut3 has been detected in numerous types of cancer, including breast, oral, lung, colon and bladder cancer, however, the underlying mechanism remains unclear (3)(4)(5)21). Given that mTORC1 signaling is also frequently activated in cancer, one hypothesis is that hyperactivated mTORC1 signaling may be responsible for the elevated Glut3 in these types of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A family of glucose transporters (Gluts) facilitates glucose movement across the plasma membranes in a tissue-specific manner, and 14 different Glut isoforms have been characterized at present (2). Glut3 is an effective glucose transporter, previous studies have demonstrated that Glut3 is upregulated in certain types of malignancy and that it is associated with poor prognosis (3,4). Downregulation of Glut3 reduces the glucose consumption of the cell and therefore cell growth rate (5).…”
Section: Introductionmentioning
confidence: 99%
“…The members of this family differ in their affinity for glucose and their effects on physiological regulation (8,9). Glucose transporter-1 (GLUT-1) is a member of the GLUT family, which is expressed in erythrocytes, endothelial cells, placenta and blood-tissue barriers, including the blood-brain and blood-nerve barriers (10,11). Recent studies have demonstrated that GLUT-1 is often upregulated in various malignant tumors, including colorectal cancer (12), esophageal cancer (13), oral squamous cell carcinoma (14), renal cell carcinoma (15) breast cancer and lung cancer (16).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the impact of Glut-1 in cancer has been studied extensively, the roles of other members of SLC2 in cancer are unknown. Glut-3 is expressed in different kinds of cancer and has been identified as a negative prognostic factor for lung cancer, endometrial cancer, and laryngeal cancer [10][11][12]. Younes et al [13] described the expression of Glut-3 in 2/8 gastric cancer samples, and it was not detected in normal gastric mucosa.…”
Section: Introductionmentioning
confidence: 99%